Direct and Rapid Detection of Mycoplasma bovis in Bovine Milk Samples by Recombinase Polymerase Amplification Assays - Li, Ruiwen; Wang, Jinfeng; Sun, Xiaoxia; Liu, Libing; Wang, Jianchang; Yuan, Wanzhe (Frontiers in Cellular and Infection Microbiology, 2021)
This study aimed to detetct Mycoplasma bovis (M. bovis) in bovine milk quickly and directly by developing and validating isothermal recombinase polymerase amplification (RPA) assays. Targeting the uvrC gene of M. bovis, an RPA assay based on the fluorescence monitoring (real-time RPA) and an RPA assay combined with a lateral flow strip (LFS RPA) were conducted. It took 20 min for the real-time RPA to finish in a Genie III at 39°C, and 15 min were required to perform the LFS RPA in an incubator block at 39°C, followed by the visualization of the products on the lateral flow strip within 5 min. Both of the two assays showed high specificity for M. bovis without any cross-reaction with the other tested pathogens. With the standard recombinant plasmid pMbovis-uvrC serving as a template, both RPA assays had a limit of detcion of 1.0 × 101 copies per reaction, equivalent to that of a real-time PCR assay. In the 65 milk samples collected from cattle with mastitis, the M. bovis genomic DNA was detected in 24 samples by both the real-time RPA and the LFS RPA assays. The developed RPA assays could detect M. bovis in bovine milk in an efficient, convenient, and credible manner as attractive and promising tools, and the assays would be helpful in the rapid response to M. bovis infection causing bovine mastitis.